Effect of the elastomer type on the microstructure and mechanical properties of polypropylene - Öksüz, M; Eroglu, M (Wiley, 2005)
In this study, the effects of the elastomer type-ethylene-propylene-diene monomer (EPDM), three kinds of ethylene vinyl acetate (EVA 9, EVA 18, and EVA 28, where the number is the vinyl acetate concentration), and styrene-butadiene-styrene-and content on the microstructure and mechanical and thermal properties of isotactic polypropylene (i-PP) blends were investigated. Five different elastomer concentrations (3, 6, 9,12, and 15 wt %) were added to i-PP to produce polypropylene/elastomer blends. The yield and tensile strengths, elastic modulus, impact strength, hardness, melt flow index (MFI), and structural properties of the blends were investigated. The tensile and yield strengths, elastic modulus, and hardness decreased gradually, whereas the impact strength and MFI increased as the elastomer content increased. As a result, with respect to the impact strength, the most effective elastomers were EPDM with 15 wt % and EVA 28 with 15 wt % for higher impact strength values. (c) 2005 Wiley Periodicals, Inc.
Keywords: compounding; elastomers; mechanical properties; poly(propylene) (PP)